2016
DOI: 10.1080/08927014.2016.1259414
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of human serum proteins adsorbed onto different titanium surfaces used in dental implants

Abstract: Titanium dental implants are commonly used due to their biocompatibility and biochemical properties; blasted acid-etched Ti is used more frequently than smooth Ti surfaces. In this study, physicochemical characterisation revealed important differences in roughness, chemical composition and hydrophilicity, but no differences were found in cellular in vitro studies (proliferation and mineralization). On the other hand, the deposition of proteins onto the implant surface might affect in vivo osseointegration. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 104 publications
0
43
0
Order By: Relevance
“…Each of these slices was digested with trypsin and loaded onto a nanoACQUITY UPLC system connected online to a SYNAPT G2‐Si MS System (Waters, Milford, MA, USA). Differential protein analysis was carried out using Progenesis software (Nonlinear Dynamics, Newcastle, UK) as described before (Romero‐Gavilán et al, ), and the functional annotation of the proteins was performed using PANTHER (http://www.pantherdb.org/) and DAVID Go annotation programs (https://david.ncifcrf.gov/). Uniprot (http://www.uniprot.org/) nomenclature was adopted to name the proteins without the ending “_HUMAN”.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these slices was digested with trypsin and loaded onto a nanoACQUITY UPLC system connected online to a SYNAPT G2‐Si MS System (Waters, Milford, MA, USA). Differential protein analysis was carried out using Progenesis software (Nonlinear Dynamics, Newcastle, UK) as described before (Romero‐Gavilán et al, ), and the functional annotation of the proteins was performed using PANTHER (http://www.pantherdb.org/) and DAVID Go annotation programs (https://david.ncifcrf.gov/). Uniprot (http://www.uniprot.org/) nomenclature was adopted to name the proteins without the ending “_HUMAN”.…”
Section: Methodsmentioning
confidence: 99%
“…From 218 identified human serum proteins, 30 were detected to be associated with bone metabolism. Of these, Apo E, antithrombin and protein C are found predominantly on sand-blasted or acid-etched Ti, whereas proteins of the complement system (C3) prefer adsorption onto smooth Ti surfaces [ 55 ].…”
Section: Titanium Surface Properties and Osteointegrationmentioning
confidence: 99%
“…Hong et al have studied the Ti properties in terms of its thrombogenic potential; it is one of the metals with high biocompatibility even though it lacks the bioactive properties . However, in previous studies of our group using mass spectrometry (LC/MS/MS), we have shown that two different Ti surface treatments, with slightly different in vivo behavior, display variations in the adsorbed first protein layer . These studies open up the exciting possibility of predicting the body reaction after implantation.…”
Section: Introductionmentioning
confidence: 99%